2010
DOI: 10.1590/s0080-62342010000200032
|View full text |Cite
|
Sign up to set email alerts
|

O perfil e a ação profissional da(o) enfermeira(o) no Centro de Atenção Psicossocial

Abstract: Trata-se de um estudo qualitativo, envolvendo quatorze enfermeiros de onze Centros de Atenção Psicossocial. Os objetivos do estudo são: caracterizar o perfil profissional do enfermeiro que trabalha no CAPS, e verificar as ações desse profissional no atual modelo de assistência à saúde mental. RESULTADOS: o sexo feminino prevalece; a maioria é formada há mais de 10 anos; a inserção na área de saúde mental se dá tardiamente, e está associada à falta de opção de trabalho e proximidade do serviço com a residência … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
23

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 2 publications
0
7
0
23
Order By: Relevance
“…3 This reality resulted in the need for the implementation of teaching practices, research and extension -by Universities and educational centers -which would cover the dynamics of society. [4][5] Moreover, professional practice in mental health was rethought, and its insertion in the new mental health services was initiated. There was, therefore, investment in the professionals' experience and qualification to work in many of the different mechanisms of the Psychosocial Care Network's (Rede de Atenção Psicossocial, RAPS), including the Psychosocial Care Centers (Centros de Atenção Psicossocial, CAPS), therapeutic homes, day-hospitals, among others, where the daily practice resulted in the need for different forms of interdisciplinary work to intervene and to take care of the mentally ill individual.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 This reality resulted in the need for the implementation of teaching practices, research and extension -by Universities and educational centers -which would cover the dynamics of society. [4][5] Moreover, professional practice in mental health was rethought, and its insertion in the new mental health services was initiated. There was, therefore, investment in the professionals' experience and qualification to work in many of the different mechanisms of the Psychosocial Care Network's (Rede de Atenção Psicossocial, RAPS), including the Psychosocial Care Centers (Centros de Atenção Psicossocial, CAPS), therapeutic homes, day-hospitals, among others, where the daily practice resulted in the need for different forms of interdisciplinary work to intervene and to take care of the mentally ill individual.…”
Section: Introductionmentioning
confidence: 99%
“…7 The important role of Universities and excellence centers in the Psychiatric Reform process is acknowledged, as well as the transition from a standard asylum disorder treatment to a psychosocial care model, with community foundations, taking into account the relevant contribution of pedagogical practices, widespread among the undergraduate courses in the health area. [3][4][5] In this model, nurses, doctors, psychologists, social workers, and others, are important agents in the implementation of better assistance to people with mental disorders and in the implementation of public policies on mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations show that professionals inserted in psychosocial care services have training with little focus on mental health and can be the result of remnants of the asylum epochs [19].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a survey of nurses from eleven Centers for Psychosocial Care showed that the insertion of these professionals in mental health occurred at a late stage of their professional careers, not being a career that was planned and built during the undergraduate course [19].…”
Section: Discussionmentioning
confidence: 99%
“…Another difficulty observed and reported in the construction of collective ideas about care and argued in other studies (26)(27)(28) was the difference between the activities developed, particularly by nursing staff and other PCC professionals. The nursing staff was concerned with giving medication, organization of the routine, use of telephone and keys, referring testing and surveillance body-to-body at the gates and other dependencies of the institution, including the expectation that they could escape.…”
Section: The Composition Of the Network (Team) And Contractuality Outmentioning
confidence: 92%